2011
DOI: 10.1007/s10856-011-4361-0
|View full text |Cite
|
Sign up to set email alerts
|

Composites for bone repair: phosphate glass fibre reinforced PLA with varying fibre architecture

Abstract: Internal fixation for bone fractures with rigid metallic plates, screws and pins is a proven operative technique. However, refracture's have been observed after rigid internal fixation with metal plates and plate fixation has been known to cause localised osteopenia under and near the plate. In the present study, resorbable composites comprising a PLA matrix reinforced with iron doped phosphate glass fibres were investigated. Non-woven random mat laminates of approximately 30% and 45% fibre volume fraction (V(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
79
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 20 publications
1
79
1
Order By: Relevance
“…The number average length obtained for the extracted fibres from the bars and rods were *1.5 and 1.2 mm, respectively. The average length of the fibres within the P50 RM rods was higher than the critical fibre length (around 0.7 mm [52]) therefore, some fibre reinforcement effect should have been conferred. It was found that the mechanical properties for discontinuous fibre reinforced composites increase as fibre length increases [53][54][55].…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…The number average length obtained for the extracted fibres from the bars and rods were *1.5 and 1.2 mm, respectively. The average length of the fibres within the P50 RM rods was higher than the critical fibre length (around 0.7 mm [52]) therefore, some fibre reinforcement effect should have been conferred. It was found that the mechanical properties for discontinuous fibre reinforced composites increase as fibre length increases [53][54][55].…”
Section: Discussionmentioning
confidence: 94%
“…7,8). Given the relative similarity of the two distributions it would appear that the majority of damage was caused during the initial random mat fabrication process and composite pressing, though there was also an Ahmed et al [52] reported that the fibre length within random mat (RM) composites produced had decreased from 10-mm (initial length) to *3 mm due to collision damage with the stirring impeller blade during the dispersion process. The number average length obtained for the extracted fibres from the bars and rods were *1.5 and 1.2 mm, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The potential advantages of glass/polymer composite scaffolds for regenerative medicine have been widely emphasized in the recent literature [8][9][10] In this work, innovative bilayered sponge-like scaffolds, based on a bioresorbable phosphate glass and a glycidoxypropyltrimethoxysilane-crosslinked network of gelatin (G) were studied in order to investigate their potential for osteochondral tissue regeneration. The proposed matrices represent a new category of bilayered scaffolds, that could be easily obtained by a single step procedure.…”
Section: Introductionmentioning
confidence: 99%